2010
DOI: 10.1109/jsac.2010.100105
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic traffic engineering for network robustness

Abstract: Abstract-The continuously increasing complexity of communication networks and the increasing diversity and unpredictability of traffic demand has led to a consensus view that the automation of the management process is inevitable. Currently, network and service management techniques are mostly manual, requiring human intervention, and leading to slow response times, high costs, and customer dissatisfaction. In this paper we present AutoNet, a self-organizing management system for core networks where robustness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 20 publications
0
74
0
1
Order By: Relevance
“…Tizghadam and Leon-Garcia [15] provided a theoretical basis for the design of the algorithm to calculate the metric, network criticality, to determine the robustness of the network. In this paper, the application was developed using this as a theoretical base [15].…”
Section: Algorithm Designmentioning
confidence: 99%
See 4 more Smart Citations
“…Tizghadam and Leon-Garcia [15] provided a theoretical basis for the design of the algorithm to calculate the metric, network criticality, to determine the robustness of the network. In this paper, the application was developed using this as a theoretical base [15].…”
Section: Algorithm Designmentioning
confidence: 99%
“…In [15], the authors showed that if the weight increases, the goodness of that link increases. The factors increasing the goodness of the link such as available bandwidth are called as "beneficial QoS parameters" and those that decrease the goodness of the link are called the "detrimental QoS parameters" such as packet loss or length of the link.…”
Section: Weight Assignmentmentioning
confidence: 99%
See 3 more Smart Citations